Design-led innovation and Circular Economy practices in regional Queensland. (June 2019) - Fleischmann, Katja
The Circular Economy proposes a sustainable economic model that encourages businesses and governments to work towards the goal of conserving natural resources and reducing waste. This model largely relies on government policies that encourage waste reduction and help businesses creating markets to re-purpose that waste profitably. Design-led innovation offers methods to drive required business model transformation and is recognized as one of the key enablers in the transition to a Circular Economy. It is evident globally that metropolitan cities and countries with high innovation indices are better able to transition to a Circular Economy by applying design-led innovation. Although more populous states and densely populated cities in Australia have started to initiate Circular Economy practices, it is unclear if similar initiatives could be developed in regional economies in Australia and if design-led innovation has a role to play in their acceptance and development. This study is an exploration into two regional areas in the state of Queensland: the Sunshine Coast and North Queensland. The qualitative study explores the views of waste managers of local councils, small-scale applications of the Circular Economy on two university campuses and an experiment to introduce a street of business owners to Circular Economy practices.